Can cost-effectiveness analysis integrate concerns for equity? Systematic review - Johri, Mira; Norheim, Ole Frithjof (International Journal of Technology Assessment in Health Care, 2012)
OBJECTIVES: The aim of this study was to promote approaches to health technology assessment (HTA) that are both evidence-based and values-based. We conducted a systematic review of published studies describing formal methods to consider equity in the context of cost-effectiveness analysis (CEA). METHODS: Candidate studies were identified through an unrestricted search of the Pub Med and EMBASE databases. The search closed on January 20, 2011. We identified additional studies by consulting experts and checking article bibliographies. Two authors independently reviewed each candidate study to determine inclusion and extracted data from studies retained for review. In addition to documenting methods, data extraction identified implicit and explicit notions of fairness. Data were synthesized in narrative form. Study quality was not assessed. RESULTS: Of the 695 candidate articles, 51 were retained for review. We identified three broad methods to facilitate quantitative consideration of equity concerns in economic evaluation: integration of distributional concerns through equity weights and social welfare functions, exploration of the opportunity costs of alternative policy options through mathematical programming, and multi-criteria decision analysis. CONCLUSIONS: Several viable techniques to integrate equity concerns within CEA now exist, ranging from descriptive approaches to the quantitative methods studied in this review. Two obstacles at the normative level have impeded their use in decision making to date: the multiplicity of concepts and values discussed under the rubric of equity, and the lack of a widely accepted normative source on which to ground controversial value choices. Clarification of equity concepts and attention to procedural fairness may strengthen use of these techniques in HTA decision making.
Keywords: Canada; Cost-Benefit Analysis; Decision Support Techniques; Health Resources; Health Services Accessibility; Health Status Disparities; Humans; Quality-Adjusted Life Years; Social Justice; Social Welfare

Cost-effectiveness with equity: Raising learning for marginalised girls through Camfed's programme in Tanzania - Sabates, Ricardo; Rose, Pauline; Delprato, Marcos; Alcott, Benjamin (Policy Paper No. 18/2 (REAL Centre, University of Cambridge, 2018), 2018)
This policy paper provides a cost-effectiveness analysis of Camfed’s programme in Tanzania. Camfed’s programme adopts a multidimensional approach that is aimed at reaching marginalised girls at risk of dropping out from secondary schools by using interventions that are aimed at both increasing their chances of staying in school and learning.
Keywords: ___working_potential_duplicate; _not_EdTechHub

Cost Effectiveness of Interactive Radio Instruction Program Karnataka: Basic and Program Cost Effectiveness - Bakshi, Shubhashansha (Working Papers, 2011)
The Program CEA extends to the study to an impact analysis of the Radio programs to assess whether the expenditure being made for this intervention is helping the students in improving their learning outcomes. This would then serve as a true measure of effectiveness that is; linking the outreach with the outcomes. This requires tracking a cohort of treatment and control groups over a period of three years. Also the study has documented the qualitative behaviour as observed in these groups. URL:[http://cbps.in/Publications.aspx].
Keywords: Attendance; CEA; Central Tendency; Cost Effectiveness; Enrolment; Interactive Radio Instruction Program; Karnataka; Qualitative analysis; Research; Teachers; cohort of treatment; data; outcomes; qualitative behaviour; school; villages

Resolving the “Cost-Effective but Unaffordable” Paradox: Estimating the Health Opportunity Costs of Nonmarginal Budget Impacts - Lomas, James; Claxton, Karl; Martin, Stephen; Soares, Marta (Value in Health, 2018)
Considering whether or not a proposed investment (an intervention, technology, or program of care) is affordable is really asking whether the benefits it offers are greater than its opportunity cost. To say that an investment is cost-effective but not affordable must mean that the (implicit or explicit) “threshold” used to judge cost-effectiveness does not reflect the scale and value of the opportunity costs. Existing empirical estimates of health opportunity costs are based on cross-sectional variation in expenditure and mortality outcomes by program budget categories (PBCs) and do not reflect the likely effect of nonmarginal budget impacts on health opportunity costs. The UK Department of Health regularly updates the needs-based target allocation of resources to local areas of the National Health Service (NHS), creating two subgroups of local areas (those under target allocation and those over). These data provide the opportunity to explore how the effects of changes in health care expenditure differ with available resources. We use 2008–2009 data to evaluate two econometric approaches to estimation and explore a range of criteria for accepting subgroup specific effects for differences in expenditure and outcome elasticities across the 23 PBCs. Our results indicate that health opportunity costs arising from an investment imposing net increases in expenditure are underestimated unless account is taken of likely nonmarginal effects. They also indicate the benefits (reduced health opportunity costs or increased value-based price of a technology) of being able to “smooth” these nonmarginal budget impacts by health care systems borrowing against future budgets or from manufacturers offering “mortgage” type arrangements.

Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Strigel, Carmen (International Journal of Educational Development, 2016)
Education policymakers are investing in information and communications technology (ICT) without a research base on how ICT improves outcomes. There is limited research on the effects of different types of ICT investments on outcomes. The Kenya Primary Math and Reading (PRIMR) study implemented a randomized controlled trial comparing the effects and cost of three interventions – e-readers for students, tablets for teachers, and the base PRIMR program with tablets for instructional supervisors. The results show that the ICT investments do not improve literacy outcomes significantly more than the base non-ICT instructional program. Our findings show that cost considerations should be paramount in selecting ICT investments in the education sector.
Keywords: Education policy; International education; Kenya; Literacy; Reading; Technology; __:import:01; __:match:final; __:matched; __:study_id:2457283; ___working_potential_duplicate; __finaldtb

Cost-Effectiveness Measurement in Development: Accounting for Local Costs and Noisy Impacts - Evans, David K.; Popova, Anna (Policy Research Working Papers, 2014)

When cost-effective interventions are unaffordable: Integrating cost-effectiveness and budget impact in priority setting for global health programs - Bilinski, Alyssa; Neumann, Peter; Cohen, Joshua; Thorat, Teja; McDaniel, Katherine; Salomon, Joshua A. (PLOS Medicine, 2017)

Planning for the Total Cost of Edtech Initiatives - edWeb (edWeb, 2019)
Strategic planning for edtech is an endless journey—and not just because of constantly evolving hardware and software. Upgrading infrastructure, device maintenance, and ongoing professional development, in addition to program and device costs, mean tech initiatives need permanent budget lines that take into account the total cost. In the edWebinar, “Strategic Technology Planning and Investment,” which is part of CoSN’s Empowered Superintendent series for edWeb, three superintendents who’ve been in the trenches for all aspects of district edtech plans discussed effective financial planning for technology.

Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Piper, Benjamin; Jepkemei, Evelyn; Kwayumba, Dunston; Kibukho, Kennedy (FIRE: Forum for International Research in Education, 2015)
Kenya is investing in information and communication technology (ICT) to improve children's learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students. All three showed significant impacts in English and Kiswahili above the results of the control group. The impacts of the three interventions were not statistically significantly different from each other. Based on the findings, we recommend that Kenyan policy makers embed ICT interventions in a larger instructional reform, using ICT to support particular instructional improvement challenges. We also suggest that policy makers incorporate empirically derived cost-effectiveness analysis into investment decisions, to ensure that ICT provides value for money.
Keywords: African Languages; Control Groups; Cost Effectiveness; ERIC, Current Index to Journals in Education (CIJE); Educational Policy; Educational Practices; Elementary Secondary Education; English (Second Language); Experimental Groups; Foreign Countries; Handheld Devices; Intervention; Kenya; Literacy; Outcomes of Education; Program Effectiveness; Randomized Controlled Trials; Reading Achievement; Student Improvement; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096974; ___working_potential_duplicate; __finaldtb

Comparative Cost-Effectiveness Analysis to Inform Policy in Developing Countries: A General Framework with Applications for Education - Dhaliwal, Iqbal; Duflo, Esther; Glennerster, Rachel; Tulloch, Caitlin (Education policy in developing countries, 2013)

Education's Effects on Individual Life Chances and On Development: An Overview - McMahon, Walter W.; Oketch, Moses (British Journal of Educational Studies, 2013)
This paper estimates the effects of human capital skills largely created through education on life's chances over the life cycle. Qualifications as a measure of these skills affect earnings, and schooling affects private and social non-market benefits beyond earnings. Private non-market benefits include better own-health, child health, spousal health, infant mortality, longevity, fertility, household efficiency, asset management and happiness. Social benefits include increased democratisation, civil rights, political stability, reduced crime, lower prison, health and welfare costs, and new ideas. Individual benefits enhance community-wide development. New ‘narrow’ social rates of return using UK Labour Force earnings correct for institutional costs, longitudinal trends and ability. The paper's objective, however, is to estimate these earnings plus non-market outcomes comprehensively without overlaps and also relative to costs. Non-market outcomes are measured by averaging regression coefficients from published studies that meet scientific standards. New UK ‘narrow’ social rates of return average 12.1 per cent for short-cycle and 13.6 per cent for bachelor's programmes. Augmented with non-market effects on life chances, they are over twice that. Short degrees are found effective for regional development and have potential for developing countries.
Keywords: ___working_potential_duplicate; cost-benefit; education and development; externalities; financing criteria; life chances; non-market benefits; qualifications; rates of return; social benefits

Education's Effects on Individual Life Chances and On Development: An Overview - McMahon, Walter W.; Oketch, Moses (British Journal of Educational Studies, 2013)
This paper estimates the effects of human capital skills largely created through education on life's chances over the life cycle. Qualifications as a measure of these skills affect earnings, and schooling affects private and social non-market benefits beyond earnings. Private non-market benefits include better own-health, child health, spousal health, infant mortality, longevity, fertility, household efficiency, asset management and happiness. Social benefits include increased democratisation, civil rights, political stability, reduced crime, lower prison, health and welfare costs, and new ideas. Individual benefits enhance community-wide development. New ‘narrow’ social rates of return using UK Labour Force earnings correct for institutional costs, longitudinal trends and ability. The paper's objective, however, is to estimate these earnings plus non-market outcomes comprehensively without overlaps and also relative to costs. Non-market outcomes are measured by averaging regression coefficients from published studies that meet scientific standards. New UK ‘narrow’ social rates of return average 12.1 per cent for short-cycle and 13.6 per cent for bachelor's programmes. Augmented with non-market effects on life chances, they are over twice that. Short degrees are found effective for regional development and have potential for developing countries.
Keywords: ___working_potential_duplicate; auto_merged; cost-benefit; education and development; externalities; financing criteria; life chances; non-market benefits; qualifications; rates of return; social benefits

The True Cost of Freemiums in Edtech - Levine, Elliott (EdTech Digest, 2019)
An industry veteran has some on-point advice about what you pay for and what you get. GUEST COLUMN | by Elliott Levine They say, “the best things in life are free,” but that is not always the case. With education technology (edtech), sometimes the cost of “free” ends up being unreasonably high in the long […]

What are the impacts and cost-effectiveness of strategies to improve performance of untrained and under-trained teachers in the classroom in developing countries? Systematic review - Orr, David; Westbrook, Jo; Pryor, John; Durrani, Naureen; Sebba, Judy; Adu-Yeboah, Christine (EPPI-Centre, Social Science Research Unit, Institute of Education, 2013)
Keywords: C:Low- and middle-income countries

Cost-Effectiveness and Affordability of Interventions, Policies, and Platforms for the Prevention and Treatment of Mental, Neurological, and Substance Use Disorders - Levin, Carol; Chisholm, Dan (Mental, Neurological, and Substance Use Disorders: Disease Control Priorities, 2016)
Since the turn of the millennium, considerable progress has been made in developing an evidence base on which interventions are effective and feasible for improving mental health in low- and middle-income countries (LMICs). Such evidence provides a critical input to the formulation of plans and priorities to address the large and growing burden of mental, neurological, and substance use (MNS) disorders. However, for successful and sustainable scale-up of effective interventions and innovative service delivery strategies, decision makers require not only evidence of an intervention’s impact on health and other outcomes, such as equity or poverty, but also evidence of its cost and cost-effectiveness. Cost data provide information relevant to the financial planning and implementation of prioritized, evidence-based strategies; cost-effectiveness analysis indicates the relative efficiency or value for money associated with interventions or innovations. The application of economic evaluation to MNS disorders has largely focused on the assessment of a specific intervention’s costs and health outcomes, relative to some comparator, which may be treatment as usual, another innovation, or no intervention. Such assessments have often been conducted alongside clinical trials, enabling health economic researchers to add resource use questions to study protocols, generate estimates of each trial participant’s health care costs, and relate these costs to primary outcome measures in the form of cost-effectiveness ratios. We review this type of economic evidence over the course of this chapter, with a particular focus on studies that have been successfully carried out in LMICs. However, the number of completed studies remains small and insufficient to inform resource allocation decisions in all the national settings where cost-effectiveness information would be valuable, including the many countries where informal or traditional health care represents the predominant model of service availability. This paucity of economic evidence reflects the overall lack of resources and infrastructure for mental health services in LMICs, including research capacity. Partly to address the paucity of cost-effectiveness trials, as well as their intrinsic specificity to the setting in which they are conducted, a broader, modeling-based approach has also been used to build up economic evidence for international mental health policy and planning. This approach includes the earlier editions of the Disease Control Priorities (DCP) project and the World Health Organization’s (WHO) CHOosing Interventions that are Cost-Effective (CHOICE) project. Such model-based studies rely on existing data, as well as several analytical assumptions; these studies have adopted an epidemiological, population-based approach that identifies the expected costs and health impacts of delivering evidence-based interventions at scale in the population as a whole, whether a specific country or an entire region. We also review this form of economic evidence and comment on important gaps in the current evidence base, as well as the relative strengths and limitations of this approach. One important limitation of conventional cost-effectiveness analysis—whether garnered through trial-based or model-based approaches—is that it is restricted to consideration of the specific implementation costs and health-related outcomes of an intervention; it does not typically extend to the nonhealth or wider economic or social value of investing in mental health innovation and service scale-up. In particular, cost-effectiveness analysis in its conventional form has little to say about the equitable distribution of costs and health gains across different groups of the target population. Incorporation of such concerns into economic evaluation represents a major objective of extended cost-effectiveness analysis, which is explored and addressed specifically in chapter 13 in this volume (Chisholm, Johansson, and others 2015). In this chapter, we review the available cost-effectiveness evidence for the different levels and underpinning strategies of the mental health care system, with a focus on information generated in or for LMICs. Based on the overall analytical framework and priority intervention matrices developed for this volume, the remainder of the chapter is presented as follows. First, we consider the economic evidence for mental health prevention and protection at the population and community levels of the health and welfare system, including legislative, regulatory, and informational measures at the public policy level (population platform), as well as school-, workplace-, and community-based programs (community platform). We then examine the economic evidence relating to the identification and treatment of MNS disorders (health care platform), focusing on the relative cost-effectiveness or efficiency of treatment programs implemented in nonspecialized versus more specialized health care settings. Finally, we assess the financial costs and budgetary implications of implementing or scaling up a set of prioritized, cost-effective interventions. Our review is based on available, published literature. A systematic search of the literature for LMICs was undertaken in PubMed to find articles published since 2000 in English. The search combined terms for specific mental health interventions with economic terms such as “cost,” “cost-effectiveness,” or “quality-adjusted life year (QALY),” as well as the names of all LMICs and their respective regions (see annex 12A for a list of search terms used to identify relevant literature). Where little or no literature was found for LMICs on interventions of potential importance, this systematic search was augmented by selective searches of the literature available since 1995 for high-income countries (HICs); however, these results are not included in the figures or tables. Annex 12B provides the search statistics. Articles included in the review were graded using the checklist of Drummond and others (2005) to generate a quality score for each article, with most studies graded between 7 and 10. Annex 12C provides a list of studies that were used to generate the tables and figures presented in this chapter. It presents detailed information on the intervention characteristics and comparators, target population group, geographic location, methodology, results, and quality scores. All cost-effectiveness results are presented in 2012 US$ except where noted otherwise. Consistent with earlier iterations of DCP, reported regional estimates refer to the World Bank’s categorization of countries by income.

Mobile-based system for cost-effective e-learning contents delivery in resource and bandwidth constrained learning environments - Mahenge, Michael P. J.; Mwangoka, Joseph W. (Knowledge Management & E-Learning: An International Journal, 2014)
The advancement in Information and Communication Technologies (ICTs) has brought opportunities for the development of Smart Cities. The Smart City uses ICT to enhance performance and wellbeing, to reduce costs and resource consumption, and to engage more effectively and actively with its citizens. In particular, the education sector is adopting new ways of learning in Higher Education Institutions (HEIs) through e-learning systems. While these opportunities exist, e-learning content delivery and accessibility in third world countries like Tanzania is still a challenge due to resource and network constrained environments. The challenges include: high cost of bandwidth connection and usage; high dependency on the Internet; limited mobility and portability features; inaccessibility during the offline period and shortage of ICT facilities. In this paper, we investigate the use of mobile technology to sustainably support education and skills development particularly in developing countries. Specifically, we propose a Cost-effective Mobile Based Learning Content Delivery system for resource and network constrained environments. This system can be applied to cost-effectively broaden and support education in many cities around the world, which are approaching the 'Smart City' concept in their own way, even with less available technology infrastructure. Therefore, the proposed solution has the potential to reduce the cost of the bandwidth usage, and cut down the server workload and the Internet usage overhead by synchronizing learning contents from some remote server to a local database in the user’s device for offline use. It will also improve the quality of experience and participation of learners as well as facilitate mobility and portability in learning activities, which also supports the all-compassing learning experience in a Smart City.https://doi.org/10.34105/j.kmel.2014.06.030
Keywords: ⛔ No DOI found

Low cost tablet enhanced pedagogy for early grade reading: Indian context - Nedungadi, Prema; Jayakumar, Akshay; Raman, Raghu (2014 IEEE Region 10 Humanitarian Technology Conference (R10-HTC), 2014)
In our research we have designed pedagogy for Low Cost Tablets (LCT) to enhance early grade reading in multigrade classrooms in rural areas of India. The use of LCT helps meet the challenge of education in areas where there is a lack of qualified tutors and shortage of computing resources. The program has been implemented with (N=38) students in tribal areas of Kerala. Reading was the most common problem with the primary children, while mathematics and reading comprehension was a major challenge for children who were in middle school. Our pilot study students were able to learn faster on their own without requiring formal training due to the ease of use and the touch based interface of LCT, and they liked the idea of repeating lessons as many times as they wished. Teachers were trained in the use of LCT for assessment and early intervention and effective ways to bring up the reading skills of the students. Our findings confirm that LCT is powerful motivator in education and has a huge potential to address the issue of school dropouts. Our proposed pedagogy for LCT and findings will be of interest to educational policy makers who are looking at LCT options such as Aakash tablets to improve literacy levels among early grade learners.

The Challenge of Education and Learning in the Developing World - Kremer, Michael; Brennen, Conner; Glennerster, Rachel (Science, 2013)
Across many different contexts, randomized evaluations find that school participation is sensitive to costs: Reducing out-of-pocket costs, merit scholarships, and conditional cash transfers all increase schooling. Addressing child health and providing information on how earnings rise with education can increase schooling even more cost-effectively. However, among those in school, test scores are remarkably low and unresponsive to more-of-the-same inputs, such as hiring additional teachers, buying more textbooks, or providing flexible grants. In contrast, pedagogical reforms that match teaching to students' learning levels are highly cost effective at increasing learning, as are reforms that improve accountability and incentives, such as local hiring of teachers on short-term contracts. Technology could potentially improve pedagogy and accountability. Improving pre-and postprimary education are major future challenges.
Keywords: ___working_potential_duplicate

The True Cost of Freemium - Ferry, Anna (CPO Magazine, 2018)

SmartIT: Total Cost of Ownership Assessment - Consortium for School Networking (2016)

Capturing Cost Data - World Bank; International Rescue Committee (World Bank, 2019)
Keywords: ⛔ No DOI found

Moving towards cost-effective delivery models of teacher coaching: evidence from field experiments in South Africa - Kotze, Janeli; Taylor, Stephen; Fleisch, Brahm (RISE, 2018)
Structured learning programmes have emerged as a promising way to address the low learning levels observed in many developing countries. The delivery model of these programmes matters, and on-site teacher coaching has been recommended to be highly effective, especially in early grade literacy. In this paper, we report on a series of government-led randomised experiments in South African primary schools that build on each other to test various models of teacher training and coaching. We find that sustained on-site coaching is more cost-effective (0.41 SD increase in test scores per USD 100) than either short coaching interventions (no significant impact) or centralized teacher training workshops (0.23 SD increase in test scores per USD 100). The ability to scale on-site coaching, however, is an open question. In the latest experiment, therefore, a virtual coaching programme was compared to on-site coaching. The focus of this paper is on the midline evaluation results from this experiment. After one year of intervention, virtual coaching was no less effective than on-site coaching at improving both the instructional practice of teachers and the targeted literacy outcomes of children. This points to the potential for technological innovations to enable wider rollout of coaching programmes, even in contexts where teachers are not familiar with new technologies.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425920; __finaldtb; ⛔ No DOI found

Supporting Parenting through Differentiated and Personalized Text-Messaging: Testing Effects on Learning During Kindergarten - Doss, Christopher; Fahle, Erin; Loeb, Susanna; York, Ben (2017)
Recent studies have shown that texting-based interventions can produce educational benefits in children across a range of ages. These studies vary in their focus from broad curricula on child development, to reminders about missing work, to steps needed in order to enroll in college. Given the potential effectiveness of texting, as well as the ease of systematically varying
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Education sector analysis methodological guidelines - UNESCO-IIEP; World Bank; UNICEF; Global Partnership for Education (2014)
The Methodological Guidelines provide methods for carrying out a comprehensive analysis of the education sector in developing countries. Volume 1 of the guidelines discusses the context for the development of the education sector, enrollment, internal efficiency, out-of-school children, cost and financing, quality, system capacity and management, external efficiency and equity.

Low Cost Mobile Phones for Large Scale Teacher - Walsh, Christopher S; Shaheen, Robina; Power, Tom; Hedges, Claire; Kahtoon, Masuda; Mondol, Sikander (2012)
Education has the power to transform societies and contribute to social and economic development. In this paper we present the mobile technologies used for teacher professional development (TPD) and communicative language teaching in English in Action (EIA). The project aims to assist 25 million people access greater social and economic opportunities through English language teaching and TPD. EIA, in partnership with the Government of Bangladesh, will work with 80,000 teachers through a work-based programme of TPD using audio and visual resources on low cost mobile phones. With access to over 700 audio files aligned with the national textbook English for Today and professional development films that explain and then illustrate successful student-centred English teaching and learning, the project has already documented significant improvement in teachers’ and pupils’ English language competency. This paper provides an account of, and rationale for, the changes in the technologies used across two phases of the project, from the iPod Nano and Touch used in the pilot study with 690 teachers (2009-2010) to the low cost Nokia C1-01 mobile phone with a micro secure digital (SD) being used in upscaling to 12,500 teachers (2012-2014). We argue the low cost alphanumeric mobile phone with micro SD cards provides unprecedented opportunities to both deliver TPD and improve teachers’ and students’ communicative English language skills. The paper considers the unique suitability mobile phones present for resource constrained education systems in developing countries. Simultaneously we highlight the need for further application and research into the use of mobile technologies, not only for large-scale TPD projects, but for a diversity of international development projects and programmes which aim to achieve sustainable change at scale.

Impact of Internet Access on Student Learning in Peruvian Schools - Kho, Kevin; Lakdawala, Leah; Nakasone, Eduardo (Working Papers, 2018)
We investigate the impacts of school-based internet access on pupil achievement in Peru, using a large panel of 5,903 public primary schools that gained internet connections during 2007-2014. We employ an event study approach and a trend break analysis that exploit variation in the timing of internet roll-out up to 5 years after installation. We find that internet access has a moderate, positive short-run impact on school-average standardized math scores, but importantly that this effect grows over time. We provide evidence that schools require time to adapt to internet access by hiring teachers with computer training and that this process is not immediate. These dynamics highlight the need for complementary investments to fully exploit new technological inputs and underscores the importance of using an extended evaluation window to allow the effects of school-based internet on learning to materialize.
Keywords: Education; ICT; Internet; Schooling

Can One Laptop Per Child Save the World's Poor? - Warschauer, Mark; Ames, Morgan (Journal of International Affairs, 2010)
The One Laptop per Child (OLPC) program is one of the most ambitious educational reform initiatives the world has ever seen. The program has developed a radically new low-cost laptop computer and aggressively promoted its plans to put the computer in the hands of hundreds of millions of children around the world, including in the most impoverished nations. Though fewer than 2 million of OLPC's XO computers have been distributed as of this writing, the initiative has caught the attention of world leaders, influenced developments in the global computer industry and sparked controversy and debate about the best way to improve the lot of the world's poor. With six years having passed since Nicholas Negroponte first unveiled the idea, this paper appraises the program's progress and impact and, in so doing, takes a fresh look at OLPC's assumptions. The paper reviews the theoretical underpinnings of OLPC, analyzes the program's development and summarizes the current state of OLPC deployments around the world. The analysis reveals that provision of individual laptops is a utopian vision for the children in the poorest countries, whose educational and social futures could be more effectively improved if the same investments were instead made on more sustainable and proven interventions. Middle- and high-income countries may have a stronger rationale for providing individual laptops to children, but will still want to eschew OLPC's technocentric vision. In summary, OLPC represents the latest in a long line of technologically utopian development schemes that have unsuccessfully attempted to solve complex social problems with overly simplistic solutions.
Keywords: ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: ___working_potential_duplicate

QALY-based cost-effectiveness analysis - Pinto-Prades, J. L; Herrero, C; Abellán, J. M (The Oxford Handbook of Well-Being and Public Policy, 2016)

One step at a time: the effects of an early literacy text-messaging program for parents of preschoolers - York, Benjamin N.; Loeb, Susanna; Doss, Christopher (Journal of Human Resources, 2019)
Large systematic differences in young children’s home learning experiences have long-term economic consequences. Many parenting programs place significant demands on parents’ time and inundate parents with information. This study evaluates the effects of READY4K!, an eight-month-long text-messaging intervention for parents of preschoolers that targets the behavioral barriers to engaged parenting. We find that READY4K! increased parental involvement at home and school by 0.15 to 0.29 standard deviations, leading to child gains in early literacy of about 0.11 standard deviations. The results point to the salience of behavioral barriers to parenting and the potential for low-cost interventions to reduce these barriers.
Keywords: C93; D91; I21

Through the looking glass: can classroom observation and coaching improve teacher performance in Brazil? - Bruns, Barbara; Costa, Leandro; Cunha, Nina (Economics of Education Review, 2018)
We conducted a randomized evaluation of a program in Brazil that provided secondary schools with classroom observation feedback and access to expert coaching. Coaching content was based on Teach Like A Champion, by Douglas Lemov, which imparts practical strategies to increase teachers’ effectiveness by maximizing time on instruction and student engagement. In treatment schools, the program raised the skills of pedagogical coordinators tasked with supporting teachers to improve instruction, increased teachers’ time on instruction, raised student engagement and produced statistically significant student learning gains. Program schools performed 0.05–0.09 SD higher in 10th grade math and Portuguese on a state test and 0.06 SD higher in Portuguese on a national high school leaving test (12th grade). High quality coaching delivered to the coordinators via Skype kept costs at $2.40 per student, making the program a cost-effective and promising strategy for school-based efforts to raise teachers’ classroom effectiveness. (I21, I25, I28, J18, O15)
Keywords: Classroom observation; Economic development; Economic impact; Educational economics; Randomization; Teacher coaching; __:import:01; __:match:final; __:matched; __:study_id:2425900; ___working_potential_duplicate; __finaldtb

Are contract teachers and para-teachers a cost-effective intervention to address teacher shortage and improve learning outcomes? - Kingdon, Geeta Gandhi; Aslam, Monazza; Rawal, Shenila; Das, Sushmita (Evidence for Policy and Practice Information and Co-ordinating Centre:Social Science Research Unit, Institute of Education, University of London, 2013)

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

Do School Electriﬁcation and Provision of Digital Media Deliver Educational Beneﬁts? First-year Evidence from 164 Tanzanian Secondary Schools - Seo, Hee Kwon (University of Chicago, 2017)

Expenditures and Revenue Management - Morrell, Lance (2017)

Impact of Education on Labour Market Outcomes in Rural and Urban India - Pradhan, K. C.; Parida, P. C.; Sarangi, Tapas (Reflecting on India’s Development: Employment, Skill and Health, 2018)
This paper examines the returns to education with respect to three labour market outcomes namely wages, employment and occupation using the National Sample Survey Office (NSSO) 68th round (2011–12) data. Wage equation (without selection bias) results point to the fact that returns to education increase at an increasing rate as the level of education increases and the impact of education is found relatively higher in the case of urban than rural areas. In case of employment, the study finds that compared to illiterates, the chances of higher educated people going to agriculture sector is less. This is true even in the case of rural areas whereas the interactive variable (education with rural dummy) is found negatively associated with employment in agriculture sector. Occupation results suggest that there is a strong association between higher education (under graduate and graduate and above) with professional occupations and less with agriculture and fishery and unskilled occupations, suggesting the need for improving education and creating quality employment opportunities in the rural areas that may help in arresting the growing urban burden.
Keywords: Education; Employment; India; Occupation; Urban-rural gap; Wages

Opportunities for Equitable Access to Quality Basic Education (OPEQ): Final Report on the Impact of the OPEQ Intervention in the Democratic Republic of Congo - Aber, J. Lawrence; Starkey, Leighann; Tubbs, Carly; Torrente, Catalina; Johnston, Brian; Wolf, Sharon; Shivshanker, Anjuli; Annan, Jeannie (2015)

The difference between economic and financial analysis for WASH services - Ross, Ian (WASHeconomics.com, 2018)
The distinction between economic analysis and financial analysis is not always straightforward. In this post I try to clarify this. Definitions I have previously defined WASH economics as “the stud…

Value for money and international development: Deconstructing myths to promote a more constructive discussion - Jackson, Penny (OECD Development Co-operation Directorate, 2012)

How ed-tech can help leapfrog progress in education - Vegas, Emiliana; Ziegler, Lauren; Zerbino, Nicolas (Brookings, 2019)
This brief analyzes the use of ed-tech innovations around the world.

What are the impacts and cost effectiveness of strategies to improve performance of untrained and under-trained teachers in the classroom in developing countries? Protocol - Pryor, John; Westbrook, Jo; Adu-Yeboah, Christine; Orr, David; Durrani, Naureen (EPPI-Centre, Social Science Research Unit, Institute of Education, University of London, 2012)

Scaling Access & Impact: Realizing the Power of EdTech - Pouezevara, Sarah; Valdivia, Ignacio Jara; Michalec, Mike; Amalia, Talitha; Fleischmann, Sybille (Omidyar Network, 2019)

The rise and fall of the PC in one chart - Booton, Jennifer (MarketWatch, 2016)

Does Education Need a QALY and Is LAYS It? - Crawfurd, Lee; Hares, Susannah; Le Nestour, Alexis; Rossiter, Jack (Center For Global Development, 2019)

Global Dataset on Education Quality : A Review and Update (2000-2017) - Patrinos, Harry Anthony; Angrist, Noam (World Bank Group, 2018)

Using technology to bring education to the most remote areas - Global Partnership for Education (2019)

English in Action: a new approach to continuing professional development through the use of mediated video, peer support and low-cost mobilephones in Bangladesh - Woodward, Clare; Griffiths, Malcolm; Solly, Mike (Innovations In The Continuing Professional Development Of English Language Teachers, 2014)
Keywords: C:Bangladesh

Interrogating Gender Divides in Technology for Education and Development: the Case of the One Laptop per Child Project in Ghana - Steeves, Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
Keywords: C: Ghana

Through the Looking Glass: Can Classroom Observation and Coaching Improve Teacher Performance in Brazil? - Bruns, Barbara; Costa, Leandro; Cunha, Nina (World Bank Group, 2017)
Keywords: ___working_potential_duplicate

Learning-Adjusted Years of Schooling (LAYS): Defining A New Macro Measure of Education - Filmer, Deon; Rogers, Halsey; Angrist, Noam; Sabarwal, Shwetlena (World Bank, 2018)
Keywords: _B:important; ___working_potential_duplicate; _final_bib; _important; _s:DFID; ⛔ No DOI found; ❓ Multiple DOI

Use of digital game based learning and gamification in secondary school science: The effect on student engagement, learning and gender difference - Khan, Amna; Ahmad, Farzana Hayat; Malik, Muhammad Muddassir (Education and Information Technologies, 2017)
This study aimed to identify the impact of a game based learning (GBL) application using computer technologies on student engagement in secondary school science classrooms. The literature reveals that conventional Science teaching techniques (teacher-centered lecture and teaching), which foster rote learning among students, are one of the major concerns in Pakistan Education system. This leads to student disengagement in science lessons eventually resulting in student absenteeism and dropouts from the schools. This study consisted of five stages: (1) examining the impact of Digital Game-Based Learning (DGBL) and gamification on engagement, learning and gender difference, and literature related to using DGBL models for instructional design; (2) planning learning activities and developing a GBL application based on a specific content in Science; (3) conducting an intervention with a sample of 72 participants of 8th grade (aged 12–15) in a low cost private school of Pakistan following quasi-experimental research framework; (4) observing behaviour and emotions of the participants during science lessons; (5) conducting pre and post tests to assess the learning outcomes of participants followed by focus groups discussion. Analysis from Friedman test, Mann-Whitney U test, and Wilcoxon Signed Rank test show that the GBL application has a positive influence on student engagement. However, GBL application was not equally effective for all students since girls outperformed boys in terms of engagement and learning outcomes. This study gives insights into the development of better educational games to promote student learning.

Inclusive Quality Education for Children with Disabilities - Singal, Nidhi; Ware, Hannah; Bhutani, Sweta Khanna (World Innovation Summit for Education & University of Cambridge, 2017)

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Developing a systemic approach to teacher education in sub-Saharan Africa: emerging lessons from Kenya, Tanzania and Uganda - Hardman, Frank; Ackers, Jim; Abrishamian, Niki; O’Sullivan, Margo (Compare: A Journal of Comparative and International Education, 2011)
While many countries in Eastern and Southern Africa are on track for meeting the Education for All targets, there is a growing recognition of the need to improve the quality of basic education and that a focus on pedagogy and its training implications needs to be at the heart of this commitment. By drawing on three East African countries, Kenya, Tanzania and Uganda, which are at different stages of development with regard to the reforming of teacher education, this paper explores the challenges and the lessons learned from each of the countries with regard to the development and strengthening of pre- and in-service training. The tension between quality, breadth and cost-effectiveness is explored together with a broader discussion of key principles to be taken into account when enhancing teacher education in the region as a whole.
Keywords: C:Kenya / Uganda / Tanzania; Education; Education for All; Education reform; Kenya; Pedagogy; Principles; Quality of education; Tanzania; Teacher education; Uganda; ___working_potential_duplicate; basic education; pre-service and in-service training; quality education; sub-Saharan Africa; teacher education reform

One Laptop per Child at home: Short-term impacts from a randomized experiment in Peru - Beuermann, Diether W.; Cristia, Julian; Cueto, Santiago; Malamud, Ofer; Cruz-Aguayo, Yyannu (American Economic Journal. Applied Economics, 2015)
This paper presents results from a randomized controlled trial whereby approximately 1,000 OLPC XO laptops were provided for home use to children attending primary schools in Lima, Peru. The intervention increased access and use of home computers, with some substitution away from computer use outside the home. Children randomized to receive laptops scored about 0.8 standard deviations higher in a test of XO proficiency but showed lower academic effort as reported by teachers. There were no impacts on academic achievement or cognitive skills as measured by the Raven's Progressive Matrices test. Finally, there was little evidence for spillovers within schools. (JEL I21, I28, J13, O15)
Keywords: ACCESS TO LAPTOPS; Academic achievement; Achievement tests; Business And Economics; EXCLUSION CRITERIA APPLIED; Elementary school students; Portable computers; Quality: H; Relevance: M; Statistical analysis; ___working_potential_duplicate; publishPDF

Monitoring and evaluation of the e-readers project in rural Tanzania - Machuve, D. Z.; Zlotnikova, I.; Nyambo, D. (Proceedings of the 2nd Pan African International Conference on Science, Computing and Telecommunications (PACT 2014), 2014)
This study provides recommendations on the monitoring and evaluation conducted for an ICT in Education project in two rural primary schools in Tanzania. The objective of the study was to evaluate the effectiveness of e-readers introduction at the schools. The e-readers introduction aimed at complementing the traditional print books. Print books are insufficient in primary schools in Tanzania; this ultimately leads to lack of reading skills in pupils and poor overall academic performance. As a conceptual framework the study adopted the InfoDev Monitoring and Evaluation framework for ICT in Education projects and adjusted it to local conditions. The study has shown that pupils at both schools considerably improved their reading skills as a result of the e-readers introduction. The introduction of e-readers also resulted in teachers and pupils being more motivated and engaged in learning. Survey results for parents demonstrate readiness on cost-sharing for acquiring the devices. This also indicates the feasibility of up-scaling the project to other schools in the country.
Keywords: E-readers; Educational institutions; ICT; ICT in Education project; InfoDev Monitoring and Evaluation framework; Monitoring; Tanzania; academic performance; computer aided instruction; cost-sharing; digital e-books; e-readers project; electronic publishing; mobile computing; mobile electronic device; pupil engagement; pupil motivation; reading skills improvement; rural Tanzania; rural primary schools; teachers

Tangerine® – Mobile Learning Assessments Made Easy - RTI International (RTI, 2016)
Since 2010, improving early grade reading has been a top priority for RTI and for many bilateral and multilateral donors, including the U.S. Agency for International Development (USAID), The World Bank, UK Aid and others. In support of this work and to improve upon paper forms of assessment, RTI developed a mobile assessment and coaching tool we dubbed Tangerine. Open source for all users, Tangerine is a first-of-its-kind software application optimized for offline data collection on low-cost Android tablets.

How solar mini-grids can bring cheap, green electricity to rural Africa - Zajicek, Charlie (odi.org, 2019)
Well-suited to small, remote communities, renewable energy mini-grids can be the most cost-effective option for rural electrification in Africa.

Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; professional development

A study of online English language teacher education programmes in distance education context in Pakistan - Farooq, Muhammad U.; Al Asmari, AbdulRahman; Javid, Choudhary Z. (English Language Teaching, 2012)
Technology-based initiatives have transformed the process of teaching and learning activities at formal institutions generally and distance education institutions particularly. Distance education is at the heart of the digital age making maximum use of the emerging technologies. Researchers have favoured computer mediated communications (CMC) for improving the quality of teacher education in developing countries by providing access to more and better educational resources. The researchers designed a CMC-ELT blended model and offered online English language teacher education courses at post-graduate level. A group of students enrolled in MA TEFL programme of Allama Iqbal Open University (AIOU) Islamabad Pakistan, was selected randomly and was guided through CMC-ELT blended model. The results of the study showed that the online support in distance education enhanced students' performance in terms of access, interaction and cost. The effective use of online support in distance education can improve the quality of English language teaching programmes in Pakistan.
Keywords: Access to Education; Blended Learning; Computer Mediated Communication; Control Groups; Costs; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Educational Quality; English (Second Language); Experimental Groups; Foreign Countries; Higher Education; Language Teachers; Masters Programs; Online Courses; Open Universities; Pakistan; Postsecondary Education; Pretests Posttests; Program Improvement; Second Language Instruction; Second Language Learning; Statistical Analysis; Student Attitudes; Student Characteristics; Teacher Education Programs; Teaching Methods; __:import:01; __:match:final; __:matched; __:study_id:2096524; __finaldtb

Early Grade Reading Study II (EGRS II) - USAID (2019)
The activity team works in partnership with the Department of Basic Education to evaluate the efficacy and cost-effectiveness of interventions focused on improving the performance of grade 1 and 2 learners in the subject English First Additional Language.

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

World Development Report 2018: Learning to realize education’s promise - World Bank (World Development Report, 2018)
World Development Report 2018: LEARNING to Realize Education’s Promise
Keywords: C:Low- and middle-income countries

Nudging in education - Damgaard, Mette Trier; Nielsen, Helena Skyt (Economics of Education Review, 2018)
Can we nudge children, adolescents and their parents to make better decisions on education? And can we nudge teachers to support and encourage better decision making? Education decisions are taken at young ages and involve immediate costs and potential, future benefits. In such settings behavioural barriers (e.g. lack of self-control, limited attention and social norms) likely influence choices and this may motivate the use of low cost ‘nudges’ to gently push behaviour in the desired direction. Our review of nudging interventions shows that while nudging often has positive effects, the greatest effects often arise for individuals affected most by the behavioural barrier targeted by the intervention. Hence understanding underlying behavioural mechanisms is crucial. Negative effects may arise in situations where nudges potentially crowd-out intrinsic motivation, if nudges pressurise individuals, or in situations where the choice architect has an insufficient understanding of behavioural mechanisms.
Keywords: Behavioural bias; Boost policies; Human capital investment

Autism screening and diagnosis in low resource settings: Challenges and opportunities to enhance research and services worldwide - Durkin, Maureen S.; Elsabbagh, Mayada; Barbaro, Josephine; Gladstone, Melissa; Happe, Francesca; Hoekstra, Rosa A.; Lee, Li-Ching; Rattazzi, Alexia; Stapel-Wax, Jennifer; Stone, Wendy L.; Tager-Flusberg, Helen; Thurm, Audrey; et al. (Autism Research: Official Journal of the International Society for Autism Research, 2015)
Most research into the epidemiology, etiology, clinical manifestations, diagnosis and treatment of autism is based on studies in high income countries. Moreover, within high income countries, individuals of high socioeconomic status are disproportionately represented among participants in autism research. Corresponding disparities in access to autism screening, diagnosis, and treatment exist globally. One of the barriers perpetuating this imbalance is the high cost of proprietary tools for diagnosing autism and for delivering evidence-based therapies. Another barrier is the high cost of training of professionals and para-professionals to use the tools. Open-source and open access models provide a way to facilitate global collaboration and training. Using these models and technologies, the autism scientific community and clinicians worldwide should be able to work more effectively and efficiently than they have to date to address the global imbalance in autism knowledge and at the same time advance our understanding of autism and our ability to deliver cost-effective services to everyone in need.
Keywords: Autistic Disorder; Developing Countries; Global Health; Health Services Accessibility; Humans; Internationality; Research; diagnosis; early detection; epidemiology; intervention

Inputs, Incentives, and Complementarities in Education: Experimental Evidence from Tanzania - Mbiti, Isaac; Muralidharan, Karthik; Romero, Mauricio; Schipper, Youdi; Manda, Constantine; Rajani, Rakesh (National Bureau of Economic Research, 2018)
We present results from a large-scale randomized experiment across 350 schools in Tanzania that studied the impact of providing schools with (a) unconditional grants, (b) teacher incentives based on student performance, and (c) both of the above. After two years, we find (a) no impact on student test scores from providing school grants, (b) some evidence of positive effects from teacher incentives, and (c) significant positive effects from providing both programs. Most importantly, we find strong evidence of complementarities between the two programs, with the effect of joint provision being significantly greater than the sum of the individual effects. Our results suggest that combining spending on school inputs (which is the default policy) with improved teacher incentives could substantially increase the cost-effectiveness of public spending on education.

Beyond the Basics: Improving Post-Primary Content Delivery through Classroom Technology - Beg, Sabrin A; Lucas, Adrienne M; Halim, Waqas; Saif, Umar (National Bureau of Economic Research, 2019)
Using an RCT in middle schools in Pakistan, we test the effect of a government- implemented in-class technology and brief teacher training intervention on student achievement in grade level mathematics and science. After only 4 months of exposure, student's combined math and science score increased by 0.3 standard deviations on both project and government tests, 59 percent more than the control group. Students were also more likely to pass the provincial high-stakes exams. Increased attendance by both students and teachers indicate technology can increase other inputs. At the 200 school scale, this program is extremely cost-effective.
Keywords: EXCLUSION CRITERIA APPLIED; Quality: H; Relevance: M

ICT for Education: A Conceptual Framework for the Sustainable Adoption of Technology-Enhanced Learning Environments in Schools - Rodriguez, Patricio; Nussbaum, Miguel; Dombrovskaia, Lioubov (Technology, Pedagogy and Education, 2012)
Currently, the use of information and communication technologies (ICT) in education does not conclusively demonstrate significant effects on learning. However, not all ICT usage models are designed to affect student outcomes. Therefore, to accurately study the impact of ICT, the concept of an educational programme supported by ICT must first be defined. The authors propose the ICT for Education (ICT4E) programme, an evidence-based framework to determine a model's ability to produce improvements before having to evaluate its results. The framework has four components: implementation, intervention, transference and total cost. Based on an explicit definition of the outcomes pursued by a given programme, this framework supports the design of its activities to promote sustainable changes in pedagogical practices in schools and calculate the programme's total cost. The authors illustrate this with a programme implemented in six countries. In Chile, the ICT4E programme forms part of the policy for educational technology, evaluating the effectiveness and scalability of such initiatives. (Contains 3 tables and 3 figures.)
Keywords: Systems Framework; ⛔ No INSPIRE recid found

Teaching and Learning Materials Financing - Read, Tony (Where Have All the Textbooks Gone?: Toward Sustainable Provision of Teaching and Learning Materials in Sub-Saharan Africa, 2015)
Suggests that no single universal cause behind the persistent under-financing of textbook provision in Sub-Saharan Africa (SSA) countries exists, but some common components include, (1) the pressure on teaching and learning materials (TLM) budgets caused by rapid enrollment growth; (2) the repeated tendency for curriculum designers to make decisions without taking into account the cost implications on the system as a whole; (3) the failure of development partner (DP) support to addressed affordability and sustainability issues; (4) the misunderstanding of ministries of education (MOEs) and DPs concerning manufacturing versus textbook cost as well as textbook versus system cost; (5) the lack of review and management of the nature and extent of fund diversion, fund misappropriation, piracy, and price mark-ups in undermining allocated TLM funding; and (6) the lack of monitoring, inspection, supervision, and financial audit systems necessary to ensure that all links in the financing and supply chain operate effectively.

Interrogating gender divides in technology for education and development: The case of the one laptop per child project in Ghana - Steeves, H. Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
Keywords: Development; Gender; Ghana; Information communication technology (ICT); Internet; ⛔ No INSPIRE recid found

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

Impact of Online Computer Assisted Learning on Education: Evidence from a Randomized Controlled Trial in China - Bai, Yu; Tang, Bin; Wang, Boya; Auden, Emma; Mandell, Blake (Rural Education Action Program (REAP), 2018)
Education of poor and disadvantaged populations has been a long-standing challenge for education systems in both developed and developing countries. In China, millions of students in rural areas and migrant communities lag far behind their urban counterparts in terms of academic achievement. When they fall behind, they often have no way to catch up. Many of their parents have neither the skills nor the money to provide remedial tutoring; rural teachers often do not have time to give students the individual attention they need. Given this, there is growing interest by both educators and policymakers in helping underperforming students catch up using computer assisted learning (CAL). While CAL interventions have been shown to be effective internationally and elsewhere in China, traditional software-based CAL programs are difficult and costly to implement. An online version of CAL (OCAL), however, may be able to bypass many of offline CAL’s implementation problems and enhance the remedial tutoring experience. Unfortunately, there is little empirical evidence on whether OCAL programs can be effective in improving the quality of rural primary school education in developing countries. The objective of this paper is to examine the impact of an OCAL intervention on the academic and non-academic performance of students and to explore the mechanism behind OCAL’s impact. Importantly, we also aim to assess the cost effectiveness of the new OCAL program versus traditional CAL interventions. To achieve these objectives, we carried out a randomized controlled trial (RCT) involving over 1650 fifth grade students in 44 schools in rural areas and migrant communities across China. Students in the 22 treatment schools attended two 40minute OCAL sessions during their computer class each week for one semester; the students in the other 22 schools were in the control group and did not receive any intervention. According to our findings, OCAL improved overall English scores of students in the treatment group relative to the control group by 0.56 standard deviations. This impact is large when compared with offline CAL programs. We found that OCAL also led to a positive change in the attitudes of students towards English learning and towards student aspirations for their future education level. We found three possible explanations for OCAL’s impact. After rejecting the possibility of the Hawthorne Effect or self-efficacy-induced changes, we believe interest-oriented stimulation is the main source of improvement among students. The chance for comparison and competition with peers, as well as customized remedial question banks tailored to each student’s individual needs, likely contributed to the measured increases in academic performance among students in our sample. Cost-effectiveness analysis showed that the OCAL program is more cost-effective than traditional offline CAL, a comparison which is significant for policymakers as it indicates high potential for OCAL program expansion.
Keywords: Quality: H; Relevance: M; ⛔ No DOI found

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientiﬁc literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; ___working_potential_duplicate; __finaldtb

Does computer-assisted learning improve learning outcomes? Evidence from a randomized experiment in migrant schools in Beijing - Lai, Fang; Luo, Renfu; Zhang, Linxiu; Huang, Xinzhe; Rozelle, Scott (Economics of Education Review, 2015)
The education of the disadvantaged population has been a long-standing challenge to education systems in both developed and developing countries. Although computer-assisted learning (CAL) has been considered one alternative to improve learning outcomes in a cost-effective way, the empirical evidence of its impacts on improving learning outcomes is mixed. This paper uses a randomized field experiment to explore the effects of CAL on student academic and non-academic outcomes for students in migrant schools in Beijing. Our results show that a remedial CAL program held out of regular school hours improved the student standardized math scores by 0.15 standard deviations and most of the program effect took place within 2 months after the start of the program. Students with less-educated parents benefited more from the program. Moreover, CAL also significantly increased the students’ interest in learning.
Keywords: China; Computer-assisted learning; Development; Education; Migration; Random assignment; Test scores

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge. [ABSTRACT FROM AUTHOR]
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; __finaldtb

Challenges Facing Adoption of Information Communication Technology (ICT) In Educational Management in Schools in Kenya - Kipsoi, Emmy; Chang'ach, Dr; Sang C, Hellen (Journal of Sociological Research, 2012)
ICT has contributed greatly to educational management in schools globally (Zhao and Frank, 2003). However, in Kenya schools hardly use ICTs to manage the quality of output, or to raise teacher productivity, or to reduce costs through analyzing spending. This is attributed to a myriad of challenges facing most schools in Kenya with regard to adoption of ICTs in educational management. This has resulted to a slow rate of adoption of technology despite its promise and potential for use in educational management in schools. As such, this paper analyses the lethargy that has surrounded education management in schools with respect to acquisition of Information Communication Technology. Education and training sector has a major role to play in the implementation of the proposed ICT policy. First, the sector itself is a major user of ICT, not only in education, training and research but also in the management of the sector. The paper argues that ICT policies must be dynamic, cost-effective, adaptable, and differentiated between sectors and between the various segments of educational management in order to contribute effectively to education management. The recommendations of this paper provide a basis for the urgent need for the integration of ICTs in educational management in schools in Kenya.

Strategies for reducing inequalities and improving developmental outcomes for young children in low-income and middle-income countries - Fernald, Lia; Alderman, Harold; Behrman, Jere; O'Gara, Chloe; Yousafzai, Aisha; Cabral de Mello, Meena; Hidrobo, Melissa; Ulkuer, Nurper; Ertem, Ilgi; Iltus, Selim (Lancet, 2011)
This report is the second in a Series on early child development in low-income and middle-income countries and assesses the effectiveness of early child development interventions, such as parenting support and preschool enrolment. The evidence reviewed suggests that early child development can be improved through these interventions, with effects greater for programmes of higher quality and for the most vulnerable children. Other promising interventions for the promotion of early child development include children's educational media, interventions with children at high risk, and combining the promotion of early child development with conditional cash transfer programmes. Effective investments in early child development have the potential to reduce inequalities perpetuated by poverty, poor nutrition, and restricted learning opportunities. A simulation model of the potential long-term economic effects of increasing preschool enrolment to 25% or 50% in every low-income and middle-income country showed a benefit-to-cost ratio ranging from 6·4 to 17·6, depending on preschool enrolment rate and discount rate.

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Oculocutaneous albinism is an inherited condition with significant health and social impact on the lives of those affected throughout sub-Saharan, including in Malawi. Myths and superstitions surrounding the condition lead to stigmatisation, rejection and misconceptions. In a participatory study, consultations with educational professionals, children with albinism and their families documented the barriers to full educational access and revealed low-cost strategies that could be implemented in mainstream schools, to minimise the effect of the visual impairment associated with albinism. These were captured in two information booklets in English and vernacular, one for children and the other appropriate for teacher training.
Keywords: Albinism; Resource centres; Special educational needs; Teacher training; Visual impairment

Pre-service teacher training in Malawi: findings of a pilot study on the viability of media players for teacher development - Carrier, Carol; Finholt-Daniel, Matt; Sales, Gregory C (International Journal of Education and Development using Information and Communication Technology, 2012)
As part of the United States Agency for International Development (USAID funded Malawi Teacher Professional Development Support project, a sub-task was the piloting of an alternative technology that could be used for improving the quality and consistency of teacher continued professional development (CPD). The pilot, which included 26 open and distance learning (ODL) student teachers, was launched in the spring of 2011 using a low-cost portable MP3 multi-purpose device. A short course on numeracy, containing 5 weekly lessons, was piloted. Each lesson consisted of one or two readings, two videos, and an assignment that directed the learner to complete tasks and document their completion using the camera and audio recorder features of the media player. The viability of using the media player for CPD was evaluated on the ease of use, effectiveness of instruction, and potential for long-term scalability. The evaluation results demonstrated that, with a small amount if initial training, the devices were easy to use and they effectively deliver instruction. Scalability, however, is critical to the long-term success of an initiative based on these or similar devices. An analysis suggests that an affordable option worth considering is the systematic, shared use of media player devices within schools. This approach could dramatically reduce the cost of using this alternative technology for ODL training to pennies per lesson. [PUBLICATION ABSTRACT]
Keywords: Distance learning; Education; Learning; Malawi; Software; Student teachers; Teacher education; Teaching; __:import:01; __:match:final; __:matched; __:study_id:2096523; __finaldtb; ⛔ No DOI found

Innovation in education: what works, what doesn’t, and what to do about it? - Serdyukov, Peter (Journal of Research in Innovative Teaching & Learning, 2017)
Purpose The purpose of this paper is to present an analytical review of the educational innovation field in the USA. It outlines classification of innovations, discusses the hurdles to innovation, and offers ways to increase the scale and rate of innovation-based transformations in the education system. Design/methodology/approach The paper is based on a literature survey and author research. Findings US education badly needs effective innovations of scale that can help produce the needed high-quality learning outcomes across the system. The primary focus of educational innovations should be on teaching and learning theory and practice, as well as on the learner, parents, community, society, and its culture. Technology applications need a solid theoretical foundation based on purposeful, systemic research, and a sound pedagogy. One of the critical areas of research and innovation can be cost and time efficiency of the learning. Practical implications Several practical recommendations stem out of this paper: how to create a base for large-scale innovations and their implementation; how to increase effectiveness of technology innovations in education, particularly online learning; how to raise time and cost efficiency of education. Social implications Innovations in education are regarded, along with the education system, within the context of a societal supersystem demonstrating their interrelations and interdependencies at all levels. Raising the quality and scale of innovations in education will positively affect education itself and benefit the whole society. Originality/value Originality is in the systemic approach to education and educational innovations, in offering a comprehensive classification of innovations; in exposing the hurdles to innovations, in new arguments about effectiveness of technology applications, and in time efficiency of education.
Keywords: Educational technology; Implementation; Innovation; Time efficiency

Open Content - Haßler, Björn; Mays, Tony (The International Encyclopedia of Digital Communication and Society, 2014)
Open content is typically digital content that allows broader use than traditionally printed or copyrighted content. Open content is freed up content, for instance through permissive licensing, such as Creative Commons. Open content includes open educational resources (OER), OpenCourseWare (OCW), open video, open access publications, as well as open data. It shares some similarity with open source software. Open content can have different freedoms, such as legal freedom, technological freedom (including usability and accessibility), as well as freedom in terms of education and participation, related to inclusion and interactive pedagogy. More broadly open content is related to open education and open educational practices. Although open content can be traced back further, the movement developed particularly rapidly in the 2000s, with major education and research stakeholders publishing open content and adopting policies promoting open content and open research practices. This entry reviews the origins of open content, and discusses different aspects of “open.” Two specific areas are highlighted: first, open content in higher education, including open textbooks, massively open online courses, open video, and research on open content, pointing to cost savings; second, open educational resources in Africa through recent developments and success stories, particularly in the context of OER Africa.
Keywords: Author:Haßler; _C:Canada CAN; _C:France FRA; _C:South Africa ZAF; _C:Spain ESP; _C:United Kingdom GBR; __C:scheme:1; dode_eth-src-dode; dode_eth-trf2-dode; open access; open education; open educational resources

Promoting Student–Teacher Interactions: Exploring a Peer Coaching Model for Teachers in a Preschool Setting - Johnson, Stacy R.; Finlon, Kristy J.; Kobak, Roger; Izard, Carroll E. (Early Childhood Education Journal, 2017)
Peer coaching provides an attractive alternative to traditional professional development for promoting classroom quality in a sustainable, cost-effective manner by creating a collaborative teaching community. This exploratory study describes the development and evaluation of the Colleague Observation And CoacHing (COACH) program, a peer coaching program designed to increase teachers’ effectiveness in enhancing classroom quality in a preschool Head Start setting. The COACH program consists of a training workshop on coaching skills and student-teacher interactions, six peer coaching sessions, and three center meetings. Pre-post observations of emotional support, classroom organization, and instructional support using the Classroom Assessment Scoring System of twelve classrooms assigned to peer coaching were compared to twelve control classrooms at baseline and following the intervention. Findings provide preliminary support that the peer coaching program is perceived as acceptable and feasible by the participating preschool teachers and that it may strengthen student–teacher interactions. Further program refinement and evaluation with larger samples is needed to enhance student–teacher interactions and, ultimately, children’s adaptive development.
Keywords: Classroom quality; Head Start; Peer coaching; Professional development; Professional learning communities; Student–teacher interactions

Learning from international experiences with interactive whiteboards - Hennessy, Sara; London, Laura (OECD, 2013)
This paper describes teacher strategies and experiences with interactive whiteboards (IWBs) and draws on the published research in this area to understand how a systemic approach to technology-based innovations in schools can contribute to quality education for all. It explores ways to support the cultural shift in teacher and learner roles that helps to integrate the technology effectively into classroom teaching. It begins by considering how the features of IWB technology might potentially be exploited in the primary or secondary school classroom to support subject teaching and learning. International experiences of implementing IWB programs are then described, mostly from the United Kingdom where integration efforts are the most prominent, and implications for future intervention efforts are examined. The review concludes by defining the organisational conditions for enhancing teacher commitment and thus the likelihood for successful change. In particular, the role of teacher professional development is foregrounded and characteristics of effective programmes are outlined. Some comments about the relative costs and benefits, and recommendations for policymakers, are made.

How behavioral science can empower parents to improve children's educational outcomes - Bergman, Peter (Behavioral Science & Policy, 2019)
Parents powerfully influence their children’s educational outcomes. Yet psychological and informational barriers impede parents’ ability to engage with their children in ways that improve outcomes: parents tend to have inflated perceptions of their children’s performance, which can deter them from taking helpful steps to effectively support their learning, and parenting is complex. Limited cognitive bandwidth for coping with complexities can steer parents’ attention away from actions that have long-term benefits for their children and toward actions yielding immediate returns. Poor school-to-parent communication and poverty exacerbate all of these problems. In this article, the author demonstrates how providing timely, actionable information to parents can lower these barriers and help parents engage with their children more productively from kindergarten through high school. Moreover, providing this information can improve educational outcomes at low cost.

Disrupting education? Experimental evidence on technology-aided instruction in India - Muralidharan, Karthik; Singh, Abhijeet; Ganimian, Alejandro J. (American Economic Review, 2019)
We study the impact of a personalized technology-aided after-school instruction program in middle-school grades in urban India using a lottery that provided winners with free access to the program. Lottery winners scored 0.37 sigma higher in math and 0.23 sigma higher in Hindi over just a 4.5-month period. IV estimates suggest that attending the program for 90 days would increase math and Hindi test scores by 0.6 sigma and 0.39 sigma respectively. We find similar absolute test score gains for all students, but much greater relative gains for academically-weaker students. Our results suggest that well-designed, technology-aided instruction programs can sharply improve productivity in delivering education.
Keywords: Analysis of Education, Returns to Education, Education: Government Policy, Human Capital; Human Development; Income Distribution; Labor Productivity, Economic Development: Human Resources; Migration; Occupational Choice; Quality: H; Relevance: H; Skills; _THEME: Teacher Professional Development; ___working_potential_duplicate; ⛔ No DOI found

Conducting Semi-Structured Interviews - Adams, William C. (Handbook of Practical Program Evaluation, 2015)
Conducted conversationally with one respondent at a time, the semi-structured interview (SSI) employs a blend of closed- and open-ended questions, often accompanied by follow-up why or how questions. About one hour is considered a reasonable maximum length for SSIs in order to minimize fatigue for both interviewer and respondent. This chapter begins with a discussion on the disadvantages and advantages of SSIs. Despite the disadvantages and costs of SSIs, they offer some extraordinary benefits as well. Semi-structured interviews are superbly suited for a number of valuable tasks, particularly when more than a few of the open-ended questions require follow-up queries. The chapter presents some recommendations that can be considered when constructing an SSI guide. All in all, effectively conducted semi-structured interviews, even though labor intensive, should be worth the effort in terms of the insights and information gained.
Keywords: SSI guide; open-ended questions; semi-structured interviews

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.

Influence of mobile learning training on pre-service social studies teachers' technology and mobile phone self-efficacies - Gloria, Adedoja; Oluwadara, Abimbade (Journal of Education and Practice, 2016)
Current instructional deliveries favour the use of mobile technology because of its inherent potentials and benefits such as portability, ease of use cost and others. Despite these benefits, many teachers especially in Sub-Saharan Africa still prefer the conventional method and use mobile phones for social engagements such as texting, chatting, callings and others. Though, these teachers use mobile phones for these social activities, using it for instruction is somewhat problematic for them without adequate training on its pedagogical implications. This is also because there are dearth of trainings in this area. Some factors that could however affect this type of specialised training include Technology Self-efficacy, Mobile Phone Self-efficacy, attitude, age and others. The sample of this present study was 101 pre-service social studies teachers in two Universities in Nigeria. The influence of the Mobile learning training on Technology/Mobile Phone Self-efficacies was explored. The results indicated that the pre-service social studies teachers have high Technology/Mobile Phone Self-efficacies after exposure to the training.
Keywords: Age Differences; ERIC, Current Index to Journals in Education (CIJE); Electronic Learning; Foreign Countries; Higher Education; Instructional Effectiveness; Likert Scales; Nigeria; Postsecondary Education; Predictor Variables; Preservice Teachers; Pretests Posttests; Questionnaires; Self Efficacy; Social Studies; Student Teacher Attitudes; Technological Literacy; Technology Education; __:import:01; __:match:final; __:matched; __:study_id:2096188; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Cloud computing architecture for eLearning in secondary schools - Mwakisole, Kennedy; Kissaka, Mussa; Mtebe, Joel (The African Journal of Information Systems, 2019)
In recent years, schools have been investing heavily on information and communications technology (ICT) infrastructure to implement eLearning systems to enhance the quality of education in secondary schools in Tanzania. The majority of these systems are implemented using a traditional web-based eLearning approach on school premises which is costly and limits usage due to lack of scalability and flexibility. Consequently, many schools have started adopting cloud computing as a solution. However, this adaption depends on well-defined cloud eLearning architecture. This study proposed cloud architecture for implementing an eLearning system in secondary schools in Tanzania by adopting various layers proposed in previous studies. The effectiveness of this proposal was evaluated by comparing its performance with a similar traditional web-based eLearning system using the Moodle benchmark tool and Apache Jmeter. The study found that eLearning systems implemented in the cloud-based infrastructure had better performance metrics than web-based eLearning systems on school premises.
Keywords: ⛔ No DOI found

MOOCs for Teacher Professional Development: Reflections and Suggested Actions - Misra, Pradeep Kumar (Open Praxis, 2018)
Teacher Professional Development (TPD) has become a major policy priority within education systems worldwide. But keeping teachers professionally up-to-date and providing them professional development opportunities on continuing basis is a big challenge. Massive Open Online Courses (MOOCs) can be a cost and resource effective means to complement the traditional methods of professional development of teachers. This optimism is based on the assumption that use of MOOCs will facilitate mass training of teachers as per their convenience and ease. The other assumption is that being MOOCs-based training, it will be easy to adapt it to different cultures and languages. Considering these assumptions, this concept paper which is based on reviews of different reports, documents and research papers - discusses the challenges of TPD, reflects upon promises of using MOOCs for TPD; details initiatives and experiences of using MOOCs for TPD; and suggests actions for promoting the use of MOOCs for TPD.

EdTech for Learning in Emergencies and Displaced Settings: A rigorous review and narrative synthesis - Tauson, Michaelle; Stannard, Luke (Save The Children, 2018)
Globally, according to UNESCO (2017), 264 million children of primary and secondary school age are out school. UNESCO also estimates that worldwide roughly 100 million young people are fully illiterate. While data on attendance, enrolment, and literacy can be difficult to gather in fragile and conflict-affected settings, estimates suggest that children in these settings are roughly three times more likely to be out of school than children living in stable, but low-income countries.
Keywords: GENERAL - to be categorised; Google Scholar/ forced displacement edtech; IMPORT_FROM_DFID_RITE; Important; Read; _THEME: Teacher Professional Development; ___working_potential_duplicate; auto_merged; ⛔ No INSPIRE recid found

An Overview of ICT for Education of Refugees and IDPs - Joynes, Chris; James, Zoe (K4D, Knowledge, Evidence, and Learning for Development, 2018)
This rapid review examined examples of ICT approaches to address the education needs of those living in IDP and refugee camps and lessons learned from these experiences. Although ICT is considered a good system to fulfil the education needs within refugee settings, many studies conclude that access to ICTs in schools or at home is not sufficient to improve learning outcomes. It is due to the role of a mentor or tutor figure is seen as key to productive learner engagement with technology, and the effectiveness of ICT-based education is reliant on appropriate teacher training to ensure successful up-take at the classroom level (Tauson & Stannard 2018: 47, 62; UNESCO 2018: 74; Carlson 2013: 30). Secondly, in terms of content, ICTs for education should provide content that is responsive or adaptable to the learners’ level, is implemented in line with the local curriculum and also is relevant to the learners’ context (Tauson & Stannard 2018: 36-38, 61). Despite this potential for ICTs, there remains a broad lack of evidence related to education in refugee settings (Burde et al. 2015; Tauson & Stannard 2018; World Bank 2016). In particular, more information is needed on pedagogic design, on the effective use of ICTs for learning, on the role of ICTs in ensuring continuity of and linkages between learning in formal and non-formal settings, on the role of ICTs in educational data-gathering, and on the cost-effectiveness of ICT-led interventions (Burde et al 2015; Tausin & Stannard 2018; Carlson 2013). In light of the availability of evidence, some of the studies cited here instead supplement their findings by drawing on observational studies, and on studies on effective ICT usage from learners in non-refugee contexts (Burde et al. 2015; Tauson & Stannard 2018).
Keywords: Google Scholar/ "education technology" refugees; RER theme_general; RER theme_pedagogies and modalities; ⛔ No DOI found

The Use of Information and Communication Technology (ICT) for Knowledge Management in the Second Cycle Educational Institutions in Ghana - Ohemeng, Patrick; Twum, Edward; Nii, Isadore (International Journal of Computer Applications, 2015)
Given its capabilities to widen access, improve the quality and reduce the cost of developing, accessing and maintaining information, Information and Communication Technology (ICT) offers increased possibilities for managing knowledge. This paper thus investigates the level of utilization of ICT in the knowledge management processes in the Ghanaian educational system. Being a descriptive study, a randomly selected sample of second cycle educational institutions was surveyed through questionnaire. Using descriptive data analysis, the study found a low level of Information and Communication Technologies usage in knowledge management processes in the second cycle educational system. Knowledge management practices were found to be inefficient due to, among other things, absence of strategic policies and nonutilization of ICT. The findings indicate that the Secondary Schools are not deriving the efficiency returns of the computers they have acquired due to the absence of a deliberate and effective strategy for knowledge management. Also students, teachers and administrators in the second cycle schools are not benefitting from the information revolution for knowledge management. It was recommended that capacity building in knowledge management and improvement of Internet speed should be given priority attention by educational authorities.

Challenge and srivers of over-Enrollment in the early years of primary school in Uganda - Weatherholt, Tara; Jordan, Rachel; Crouch, Luis; Barnett, Ed; Pressley, Jennifer (International Journal of Early Childhood, 2019)
Consistent over-enrollment, together with low official repetition rates, in the early years of school indicates inaccurate reporting of repetition, which may mask the reasons for low primary school completion. Actual repetition rates may be higher and pose issues for teachers through overcrowding of classrooms and issues for governments through inefficient education systems. This research explores repetition rates of students in Primary 1 in Uganda and considers the implications for efficiency and quality of education for the early years of school. The sample comprised 1440 students in Primary 1 classrooms in 120 schools. Interviews were conducted with 1318 caregivers of randomly selected students and 1439 teachers of the same students, and official records from 118 schools were examined to compare age and repetition rates. Findings showed that caregiver- and teacher-reported repetition is much higher than officially reported by schools; that repetition is strongly linked to non-attendance in pre-primary schooling; and that caregivers reported more over-age students, fewer target-age students, and more under-age students than official school records. Policy implications include the need for dialogue around repetition rates and the possible efficiency effects of less-costly, pre-primary education on the total primary schooling cycle.
Keywords: Early childhood; Education efficiency; Low-income countries; Pre-primary education; Repetition

Experimenting with Automatic Text-to-Diagram Conversion: A Novel Teaching Aid for the Blind People - Mukherjee, Anirban; Garain, Utpal; Biswas, Arindam (Journal of Educational Technology & Society, 2014)
ABSTRACT Diagram describing texts are integral part of science and engineering subjects including geometry, physics, engineering drawing, etc. In order to understand such text, one, at first, tries to draw or perceive the underlying diagram. For perception of the blind students such diagrams need to be drawn in some non-visual accessible form like tactile graphics. Technologies for producing tactile graphics are available but they are too expensive to be afforded by the blind students or schools in developing countries like India. As a result, science education for a large population of blind students is severely compromised. This paper proposes a novel solution to this problem. A method for digital to Braille mapping of geometry diagrams on the low-cost traditional Braille text printer is reported here. Later on, this is integrated with a previously developed text-to-diagram conversion system. Using the integrated system, a blind student can input a geometry word problem and perceive the underlying diagram on a Braille printout. The major part of the study involves rigorous evaluation of the system at a Blind school. The enthusiasm and the ability shown by the subjects in using the system strongly attest its viability as an effective teaching/learning tool for the blind students.
Keywords: ⛔ No DOI found

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Social media use by undergraduate students of education in Nigeria: a survey - Wickramanayake, Lalith; Muhammad Jika, Saidu (The Electronic Library, 2018)
Purpose This paper aims to investigate teacher students’ perceptions, intentions, experiences, attitudes, opinions and barriers concerning social media use and impact of social media on their learning process. Design/methodology/approach A stratified sampling technique was applied to draw the sample, and 242 teacher students were selected as a sample from three higher educational institutions in Gombe State, Nigeria. A questionnaire survey method was used to collect the data. Data analysis was by means of simple and inferential statistics. Findings The students widely used mobile phones to access social media, and social media was extremely popular for education, entertainment and communication among them. Educational and informational communities were also preferred by students to other social media communities. The study further revealed that effective social media usage among students enhanced their different types of skills including learning. Unstable electricity connections, security and privacy issues, internet costs and unreliable internet connections were recorded as some barriers concerning students’ social media use. Originality/value The outcome of this study will be a unique contribution because the pertinent literature provides little evidence or research highlights concerning teacher students’ social media use. Even more, the results of the present study may be a useful resource for university administrators, education policymakers and innovative teachers in universities – especially in developing countries and particularly Nigeria – when considering integration of modern techniques and technologies with university teaching and learning.
Keywords: Internet-based learning; Media-based teaching; Nigeria; Social media; Teaching students; User studies

Computers and the academic performance of elementary school-aged girls in China's poor communities - Yang, Yihua; Zhang, Linxiu; Zeng, Junxia; Pang, Xiaopeng; Lai, Fang; Rozelle, Scott (Computers & Education, 2013)
Experts agree that computers and computing play an important role in education. Since the 1980s there has been a debate about gender as it relates to computers and education. However, results regarding gender differences concerning computer use in education are not consistent. In particular there is little work done in China on this issue. Therefore, the overall goal of this paper is to demonstrate whether girls and boys can gain equally from computer-based education in China's elementary schools. To do so we analyze results from three randomized field experiments of a Computer Assisted Learning (CAL) program and One Laptop Per Child (OLPC) program. The field experiments are carried out in three kinds of schools: Shannxi rural public schools; Qinghai minority public schools; and Beijing migrant schools. Although CAL and OLPC have been considered cost effective means to improve learning outcomes, it is not known whether the programs impact girls differently than boys. Our analysis shows that, in fact, there were no differences between female and male students in either the improvement in standardized math test scores or Chinese test scores with either the CAL or OLPC programs. Our study suggests that among disadvantaged students in China's rural areas and migrant communities, there is reason to believe that computer based learning can benefit both girls and boys equally. This finding has possible implications for China's ongoing efforts to integrate computers and computing technologies into the nation's underserved schools.
Keywords: Country-specific developments; Elementary education; Evaluation of CAL systems; Gender studies; Teaching/learning strategies

Growth prospects, market challenges and policy measures: Evolution of mobile broadband in Pakistan - Hanif, Muhammad Shehzad; Yunfei, Shao; Hanif, Muhammad Imran (Digital Policy, Regulation and Governance, 2018)
Purpose The paper aims to explore the long-term prospects of mobile broadband adoption in a developing country. The supply-side and demand-side policy measures are recommended to counter the challenges to broadband adoption. Design/methodology/approach Methodologically, this study uses document analysis to explain secondary data including growth statistics, trade literature and previous scholarly research. Based on the growth statistics of broadband and the informed market insights, the research discusses the prevailing market threats and recommends counter measures to improve the long-term prospects of broadband propagation. Findings The growth of mobile broadband is settling down in Pakistan due to various barriers like cost, literacy, security and unavailability of local content. Collaborative efforts are required by the government, the service providers and the people to enhance the adoption of broadband service and secure economic benefits of the broadband. Practical implications The research offers useful implications for managers and policymakers in Asian and African developing countries; the policy measures discussed here may serve as guidelines for them in the design of their own policies regarding broadband supply and demand. Originality/value The study makes an effort to examine the broadband growth in a developing country on the basis of both quantitative and qualitative aspects. The research endeavors to fill the gap on the particular scholarship of research covering potential uptake of broadband services and the effects of constraining elements to broadband adoption in a developing country.

Computers and the academic performance of elementary school-aged girls in China's poor communities - Yang, Yihua; Zhang, Linxiu; Zeng, Junxia; Pang, Xiaopeng; Lai, Fang; Rozelle, Scott (Computers & Education, 2013)
Experts agree that computers and computing play an important role in education. Since the 1980s there has been a debate about gender as it relates to computers and education. However, results regarding gender differences concerning computer use in education are not consistent. In particular there is little work done in China on this issue. Therefore, the overall goal of this paper is to demonstrate whether girls and boys can gain equally from computer-based education in China’s elementary schools. To do so we analyze results from three randomized ﬁeld experiments of a Computer Assisted Learning (CAL) program and One Laptop Per Child (OLPC) program. The ﬁeld experiments are carried out in three kinds of schools: Shannxi rural public schools; Qinghai minority public schools; and Beijing migrant schools. Although CAL and OLPC have been considered cost effective means to improve learning outcomes, it is not known whether the programs impact girls differently than boys. Our analysis shows that, in fact, there were no differences between female and male students in either the improvement in standardized math test scores or Chinese test scores with either the CAL or OLPC programs. Our study suggests that among disadvantaged students in China’s rural areas and migrant communities, there is reason to believe that computer based learning can beneﬁt both girls and boys equally. This ﬁnding has possible implications for China’s ongoing efforts to integrate computers and computing technologies into the nation’s underserved schools.

Providing access to education in Sub-Saharan countries through Content-Oriented technology - Kiboro, Angelica; Bailey, Sheena; Nair, Mrinay; Salam, Tomisin; Dwhytie, Alex (2014 IEEE Canada International Humanitarian Technology Conference - (IHTC), 2014)
Access to education has been a growing concern for children in developing economies, namely lack of access to quality customized online content in the classroom and at home; lack of tools that make learning fun and effective in key subject areas; and lack of state resources to meet educational demands. The Rumie Initiative was founded to tackle these concerns. It is a non-profit organization bringing educational content to the world's underprivileged children through low-cost technology. The Rumie Initiative's vision is to redefine the way education is provided, and through this, significantly reduce poverty and drive economic development. The primary advantage of The Rumie Initiative over all other educational technology solutions is that its content is specifically tailored to meet the local educational needs and curriculum standards. Utilizing the vast reserves of free online updated educational content available today; these android driven tablets are an affordable and intuitive way to deliver pre-loaded content without the requirement of internet access. Through mass global volunteerism, The Rumie Initiative collaborates with educators in choosing appropriate educational content and distributes content-loaded tablets through local Non-Governmental Organizations, communities and government entities. The Rumie Initiative has started a program of trials around the world and recently received a positive response at a Computer - Based Math Education Summit in New York hosted by UNICEF from November 21st to 22nd 2013. The initiative was first launched in Haiti on 25th October 2013 and has since, been gaining momentum, currently exploring opportunities in Sub-Saharan countries such as Ghana, Kenya, Uganda, Rwanda, Burundi, South Africa and Nigeria. This paper focuses on The Rumie Initiative's unique business model to reach the masses, emphasizing issues relating to the power of volunteer ism, the forging of strategic development partners, and content-oriented technologies in increasing access to education.
Keywords: Blogs; Communities; Education; Internet; Internet access; Monitoring; Organizations; Rumie initiative; Servers; Terminology; authorisation; computer aided instruction; content management; content-oriented technology; curriculum standards; economics; economies; educational content; educational demands; government entities; non-governmental organizations; online content; standards; sub-Saharan countries

A framework for an ICT-based development program for science teachers in state universities and colleges in region VI - Magallanes, Amel Lavezores; Lavezores, Amel (Universal Journal of Educational Research, 2014)
Curriculum reform is central to the aspirations of many developing countries as they strive to deliver a quality education to their citizens. In State Universities and Colleges in Region VI, with its remarkable achievement of a high literacy rate in a few decades, the next step is bringing its resources to bear on providing a quality education so that Filipino science professors and students may take their places in the global labor force. This study concerns the integration of information and communications technologies (ICT) into the science curriculum of Higher Education Institutions in State Universities and Colleges in the Philippines particularly in Region VI, and the training and development requirements of science professors in this regard. A mixed methodology was employed to obtain qualitative data from 11 policy makers as represented by the Vice President of Academic Affairs of the SUC's in region VI, and quantitative data from a questionnaire for which 139 replies were received from SUC's science professors in Region VI.The findings of this study confirmed those citations in the literature that inefficient management planning and inadequate resources influence the integration of ICT in the science curriculum. Furthermore, the qualitative and quantitative findings confirmed that teachers' access to training is affected by time constraints, ineffective ICT course material, unavailability of ICT infrastructures and facilities, and high cost of ICT trainings. The policy makers interviewed in this study perceived the teachers as having a positive attitude toward ICT integration in the science curriculum, quantitative data from the teachers pointed to a high interest in ICT integration, and their willingness to pursue further professional development in the effective use of ICT in the science curriculum. Furthermore, age factor exhibited a significant difference in ICT skills, utilization and individual barriers of science teachers in SUC's Region VI. The length of service also showed a very significant difference as to the ICT skills, utilization attitudes, and individual barriers of the teacher respondents. However, as to their gender and highest educational attainment, home location and school location, there was no such factor implicating a non-significant difference in the attitudes, skills, utilization and perceived barriers.
Keywords: Barriers; College Faculty; College Science; Computer Literacy; Computer Uses in Education; ERIC, Current Index to Journals in Education (CIJE); Foreign Countries; Higher Education; Information Technology; Mixed Methods Research; Philippines; Postsecondary Education; Science Teachers; State Colleges; State Universities; Teacher Attitudes; Technology Integration; Training

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Digital literacy for children — 10 things to know - UNICEF (2019)
Digital literacy goes beyond technical know-how. It refers to the knowledge, skills and attitudes that allow children to be both safe and empowered in an increasingly digital world. This encompasses their play,  participation, socializing, searching and learning through digital technologies. What constitutes digital literacy will vary according to children’s age, local culture and context.   Children need to be digitally literate even when they are not online. Facial scanning and artificial intelligence-based profiling increasingly affect children’s lives. Children’s schooling, social welfare and future job opportunities may depend on how well they understand the digital world around them.   Digital literacy is a growing part of any approach to skills development. It features in UNICEF’s framework which seeks to prepare children and adolescents for school, work and life. In addition to digital literacy, other interconnected skills for UNICEF are: foundational skills (literacy and numeracy); transferable skills (also known as life skills, 21st-century skills or soft skills); and job-specific skills (technical and vocational skills).   Tools to develop and assess digital literacy are proliferating. A number of digital competence frameworks have been developed by both international agencies and companies. Frameworks are a necessary starting point as they define the boundaries of what constitutes digital literacy and inform curricula and assessments. Despite using a range of labels (e.g. digital literacy, skills, citizenship), they broadly converge around the idea of a set of competencies that include technical as well as transferable skills, such as communication and problem solving.   Yet most existing tools place little emphasis on children. Digital literacy definitions usually focus on citizens of all ages and not on children specifically. UNICEF believes there is a need to focus more on digital literacy for children, who have unique needs. In this area, there is a slow change from a risk and safety paradigm towards rights-based approaches that favour expression, play and development.   Few programmes operate at scale or have been evaluated for impact. One contributing factor is the lack of global consensus and standards that makes it difficult for governments and other stakeholders to design and implement comparative and cost-effective initiatives, especially within developing countries.   Similarly, UNICEF programmes would benefit from greater coordination. While UNICEF has delivered a range of digital literacy programmes at the request of governments, a survey of 40 initiatives carried out by 37 Country Offices shows they are not well coordinated with each other, and knowledge is not systematically generated or shared about efficacy and impact.   Implementing digital literacy is not easy. According to the Country Offices surveyed, key barriers to digital literacy programming are: lack of teachers’ and trainers’ capacity; lack of ICT infrastructure; low connectivity (especially for remote areas); and a lack of understanding from decision-makers. The Country Offices are asking for policy development support, digital literacy frameworks, curriculum guidelines and practical tools, such as training manuals and toolkits.   Some existing digital literacy frameworks or tools suit UNICEF well. These include the DigComp framework of the European Commission and the Digital Kids Asia-Pacific framework developed by the UNESCO Asia and Pacific Regional Office in Bangkok. If using existing digital literacy frameworks, UNICEF can add value by focusing on children.   Digital literacy programmes should be context-driven. Implementing digital literacy programmes effectively requires more than simply importing a good programme from elsewhere. Beyond choosing a framework, an integrated approach to digital literacy involves undertaking a preliminary diagnostic review of the local context, developing operationalization guidelines and conducting impact assessments.

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode